66.3k views
15 votes
Simplify the expression

Simplify the expression-example-1

1 Answer

7 votes

Answer:

A.
{x}^(3) - x - (6)/(2x + 3)

Explanation:


\frac{2 {x}^(4) + 3 {x}^(3) - 2 {x}^(2) - 3x - 6}{2x + 3} \\ \\ = \frac{(2 {x}^(4) + 3 {x}^(3) ) - (2 {x}^(2) + 3x) - 6}{2x + 3} \\ \\ = \frac{ {x}^(3) (2 {x} + 3 ) - x(2 {x} + 3) - 6}{2x + 3} \\ \\ = \frac{ {x}^(3) (2x + 3)}{2x + 3} - (x(2x + 3))/(2x + 3) - (6)/(2x + 3) \\ \\ \purple { \bold{= {x}^(3) - x - (6)/(2x + 3) }}

User Popoy
by
5.0k points